Color capital: Examining the racialized nature of beauty via colorism and skin bleaching - Ellis, Natasha P.; Destine, Shaneda (Sociology compass, 2023)
Colorism, like whiteness is capital, is rooted in the institution of slavery and has resulted in the preference of light skin. Because colorism is part of the historical construction of whiteness, the consumption of whiteness is commodified through various markets. Current manifestations of racialized beauty, that is, skin bleaching and photo editing apps such as FaceTune and Snap Chat reinforce colorism and impact conceptualizations of beauty. This literature review surveys how colorism and racialized beauty are reproduced to reinforce whiteness as a form of capital.